Effectiveness of the use of authentic materials in the foreign language acquisition process. - Arias Duque, Rodrigo; Duque Mejía, Alvaro; René Mitchell, Yanik (Íkala, Revista de Lenguaje y Cultura, 1996)
Among foreign language (FL) teaching specialists there is a deep methodological schism regarding the type of material to be used in the classroom, designed exclusively for the purpose of introducing some linguistic element for learning by the learners of the foreign language - guide text type) and authentic type materials (i.e. non-graded material, produced by the speakers of this language and for the users of this language, without any modification, and without the purpose of serving for instruction in FL, e.g. movies, magazines, newspapers, etc.): films, magazines, newspapers, etc.).